A Novel SHMPWM Technique for Sensorless Control in High-Power PMSM. (18th February 2015) - Yu, Yanjun; Gao, Lixiao; Liu, Yue; Chai, Feng; Cheng, Shukang
Abstract : In view of the low switching frequency restriction of high-power permanent magnet synchronous motor (PMSM) drive system and longing for sensorless control in hostile conditions, a novel PWM control scheme, born out of selective harmonic mitigation pulse width modulation (SHMPWM) technique, was proposed for sensorless control of high-power PMSM. A new enhanced constraint was placed on the traditional SHMPWM nonlinear transcendental equation to selectively generate constant amount of a certain3 k + 1 order harmonic signals while guaranteed that the undesired harmonic signals can be suppressed. At the same time, the3 k + 1 order harmonic signals were extracted by band-pass filter, which had the constant amplitude and phase angle difference of 120°, equivalent to inject rotating voltage vector in the natural coordinate system of motor, and the rotor position can be estimated using the3 k + 1 order harmonic signals. The nonlinear transcendental equation of the novel modulation technique had been designed, and its numerical method had been analyzed. The rotor position observer had been designed according to the3 k + 1 order harmonic signals. Simulation results verify that the harmonic suppression of the system was implemented, and the sensorless control was efficient by the novel SHMPWM technique.